Multiple sclerosis and stroke: a systematic review and meta-analysis - Hong, Ye (BMC Neurol, 2019)
BACKGROUND: Multiple sclerosis (MS) and stroke are two common causes of death and disability worldwide. The relationship between these two diseases remains unclear. Effective early preventative measures and treatments are available to reduce the morbidity and mortality of acute stroke. The objectives of our systematic review are to estimate the risk of stroke in patients with MS and to collate related studies to draw preliminary conclusions that may improve clinical practice. METHOD: Relevant studies were systematically searched in MEDLINE, Embase, the Chinese Biomedical Literature Database (CBM), the China National Knowledge Infrastructure and the VIP database of Chinese periodicals from January 1983 to May 2017, with no restrictions on language. Patients included in this review were adults who suffered from MS. Review Manager 5.3 software program was used to pool data and calculate the risk ratio (RR) and its 95% confidence interval (CI). We also performed heterogeneity and sensitivity analyses and evaluated bias in the meta-analysis. RESULTS: Nine studies including more than 380,000 participants that met our inclusion criteria were incorporated into the meta-analysis. During different follow-up periods, patients with MS had an increased risk of any type of stroke [RR = 3.48, 95% CI (1.59, 7.64), P = 0.002 for 1 year; RR = 2.45, 95% CI (1.90, 3.16), P < 0.00001 for 10–13 years]. The total prevalence of stroke (any type) in patients with MS exceeded expectations compared to different groups [Comparing with general veteran: RR = 2, 95% CI (1.19, 3.38), P = 0.009. Comparing with general population: RR = 2.93, 95% CI (1.13, 7.62), P = 0.03]. Furthermore, ischemic stroke was particularly more common in the MS population than in people without MS [RR = 6.09, 95% CI (3.44, 10.77), P < 0.00001]. CONCLUSION: Compared with the general population, people with MS have an increased risk of developing any type of stroke and ischemic stroke in particular. Consistent results were obtained from patients of different sexes and age groups. Preventative measures and treatments should be administered at earlier time points to improve patient outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12883-019-1366-7) contains supplementary material, which is available to authorized users.